Cr3+ Doping Effects on Structural, Optical, and Morphological Characteristics of BaTiO3 Nanoparticles and Their Bioactive Behavior - Efracio Mamani Flores; Bertha Silvana Vera Barrios; Julio César Huillca Huillca; Jesús Alfredo Chacaltana García; Carlos Armando Polo Bravo; Henry Edgardo Nina Mendoza; Alberto Bacilio Quispe Cohaila; Francisco Gamarra Gómez; Rocío María Tamayo Calderón; Gabriela de Lourdes Fora Quispe; Elisban Juani Sacari Sacari (Crystals, 2024)
This study investigates the effects of chromium (Cr3+) doping on BaTiO3 nanoparticles synthesized via the sol–gel route. X-ray diffraction confirms a Cr-induced cubic-to-tetragonal phase transition, with lattice parameters and crystallite size varying systematically with Cr3+ content. UV–visible spectroscopy reveals a monotonic decrease in bandgap energy from 3.168 eV (pure BaTiO3) to 2.604 eV (5% Cr3+-doped BaTiO3). Raman and FTIR spectroscopy elucidate structural distortions and vibrational mode alterations caused by Cr3+ incorporation. Transmission electron microscopy and energy-dispersive X-ray spectroscopy verify nanoscale morphology and successful Cr3+ doping (up to 1.64 atom%). Antioxidant activity, evaluated using the DPPH assay, shows stable radical scavenging for pure BaTiO3 (40.70–43.33%), with decreased activity at higher Cr3+ doping levels. Antibacterial efficacy against Escherichia coli peaks at 0.5% Cr3+ doping (10.569 mm inhibition zone at 1.5 mg/mL), decreasing at higher concentrations. This study demonstrates the tunability of structural, optical, and bioactive properties in Cr3+-doped BaTiO3 nanoparticles, highlighting their potential as multifunctional materials for electronics, photocatalysis, and biomedical applications.